Metabolic syndrome, haemostasis and thrombosis - Alessi, Marie-Christine; Juhan-Vague, Irène (Thrombosis and Haemostasis, 2008)
The metabolic syndrome (metS), a concurrence of abdominal fat, disturbed glucose and insulin metabolism, dyslipidemia, and hypertension has been strongly associated not only with subsequent development of type 2 diabetes but also with athero-thrombosis. The physiopathology of this association is complex. The metS affects the thrombogenicity of circulating blood. Apart from its effect on platelets, a procoagulant and hypofibrinolytic state has been identified; mainly the result of the inflammatory state, dyslipidemia, and liver fat accumulation that accompany the MetS. Among haemostasis disturbances, the strong rise in the inhibitor of plasminogen activator type 1 plasma level is the most documented abnormality implicating the participation of the oxidative stress and inflammatory state developed during the metS. Endothelial dysfunction is also a central feature. Moreover, secretion products of fat tissues (adipokines) are now thought to have direct modulating effects on the vascular and the circulating cells. In support of these data, the metS, may predispose not only to atherosclerosis but also to venous thrombosis.
Keywords: Haemostasis; metabolic syndrome; visceral obesity; platelet; coagulation; fibrinolysis; endothelial dysfunction